KAJIAN OZONISASI (O3) TERHADAP KARAKTERISTIK KUBIS BUNGA {Brassica oleracea var. botrytis) SEGAR SELAMA PENYIMPANAN PADA SUHU DINGIN - Ali Asgar; A T Sugiarto; Sumartini Sumartini; D Ariani (BERITA BIOLOGI, 2011)
The aims and objectives of this study are to determine the effect of ozonization on the characteristics of cauliflower (Brassica oleraceae var.botrytis) during cold storage.The benefit of this research is to prolong the storage period of cabbage flowers with characteristic and quality be appropriate to consumers. The design used is the Randomized Block Design with 6 replications. The treatments consisted of 0 ppm ozone concentration bear leaves, 1.5 ppm ozone concentration without leaves, 1.5 ppm ozone concentration bearing leaves, and 1.5 ppm ozone concentrations without leaves.The parameters observed were weight loss, hardness, moisture content, vitamin C, heavy metals Hg and Ag,number of microorganisms, organoleptic color, freshness and appearance. The results showed that the best treatment was 1.5 ppm ozoneconcentrations with cabbage flowers and leaves. This was caused by ozone acts in sterilization (ozone can kill a variety of pathogenic microorganisms such as bacteria, viruses and fungi), deodorant (ozone eliminating odors caused by a variety of organic compounds and microorganisms), decoloration (ozone can eliminate organic color), and degradation (ozone can break down various organic compounds and heavy metals).